The potential use of the Penicillium chrysogenum antifungal protein PAF, the designed variant PAFopt and its γ‐core peptide Pγopt in plant protection. Issue 5 (24th March 2020) - Tóth, Liliána; Boros, Éva; Poór, Péter; Ördög, Attila; Kele, Zoltán; Váradi, Györgyi; Holzknecht, Jeanett; Bratschun‐Khan, Doris; Nagy, István; Tóth, Gábor K.; Rákhely, Gábor; Marx, Florentine; et al.
Summary: The prevention of enormous crop losses caused by pesticide‐resistant fungi is a serious challenge in agriculture. Application of alternative fungicides, such as antifungal proteins and peptides, provides a promising basis to overcome this problem; however, their direct use in fields suffers limitations, such as high cost of production, low stability, narrow antifungal spectrum and toxicity on plant or mammalian cells. Recently, we demonstrated that a Penicillium chrysogenum ‐based expression system provides a feasible tool for economic production of P. chrysogenum antifungal protein (PAF) and a rational designed variant (PAF opt ), in which the evolutionary conserved γ‐core motif was modified to increase antifungal activity. In the present study, we report for the first time that γ‐core modulation influences the antifungal spectrum and efficacy of PAF against important plant pathogenic ascomycetes, and the synthetic γ‐core peptide Pγ opt, a derivative of PAF opt, is antifungal active against these pathogens in vitro . Finally, we proved the protective potential of PAF against Botrytis cinerea infection in tomato plant leaves. The lack of any toxic effects on mammalian cells and plant seedlings, as well as the high tolerance to harsh environmental conditions and proteolytic degradation further strengthen our concept for applicability of these proteins and peptide in agriculture. Abstract : The emerging number of crop losses due to infection or contamination caused by pesticide‐resistant pre‐ and post‐harvest plant pathogenic fungi urges the need for the development of fundamentally new and safe antifungal strategies in the agriculture, and the cysteine‐rich, highly stable antifungal peptides and proteins from filamentous ascomycetes are promising candidates in this respect. We report for the first time that γ‐core modulation influences the antifungal spectrum and efficacy of Penicillium chrysogenum antifungal protein (PAF) against important plant pathogenic ascomycetes, and the synthetic γ‐core peptide Pγ opt, a derivative of an engineered variant of PAF is antifungal active against these pathogens. We also prove the protective potential of PAF against Botrytis cinerea infection in tomato plant leaves, and the potential applicability of PAF, and its engineered variant as biofungicides in the agriculture as they do not show any toxic effects on mammalian cells and plant seedlings, and they have high tolerance to harsh environmental conditions and proteolytic degradation.